Finland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Finland's public sector balance sheet. The public sector balance sheet approach expands analysis of public finances beyond government debt to also include government assets, public corporations, and pension liabilities. For Finland, it shows that static public sector net worth is negative at some 160 percent of GDP. This implies that Finland's future fiscal balances and policies will have to be sufficiently strong to compensate, and also to address future spending pressures from rising health and long-term care. The intertemporal balance sheet shows that Finland's current medium-term fiscal framework meets this criterion-but only if health and social services reform achieves the targeted savings in public spending during the 2020s. In light of numerous risks it would be prudent to use the present economic upswing to make early headway in rebuilding buffers. Finland has a track record of prudent fiscal policy. During good economic times, the authorities have run sizable fiscal surpluses.